ANALISIS FAKTOR YANG MEMPENGARUHI PENYUSUNAN LAPORAN KEUANGAN PADA KOPERASI PRODUSEN TALENTA INOVASI MUDA DI KABUPATEN LANDAK - Konstansia, Ella; Dwi Widyastuti, Reni; Setiawan, Aris; Fakhrul Yahya, Rizky (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
This study focuses on discussion the factors that influence the preparation of financial statement at the Koperasi Produsen Talenta Inovasi Muda in Kabupaten Landak. The analysis method used qualitative form data collection techniques of observation, interviews, documentation, literature studies, and questionnaires. This study aims to determine factors influence the preparation of financial statement in Koperasi Produsen Talenta Inovasi Muda. The data processed in this study is the financial statement of the Koperasi Produsen Talenta Inovasi Muda for 2021. The financial statement is analyzed whether the financial statement is in accordance with SAK ETAP. Based on the results of the Financial Statement Analysis, out that there are items that are not in accordance with SAK ETAP, meaning that in the preparation of the financial statement for Koperasi Produsen Talenta Inovasi Muda it is not in accordance with SAK ETAP.